Oxford desk reference major trauma - Smith, Jason; Greaves, Ian; Porter, Keith M. (Oxford desk reference series, 2011)
The Oxford Desk Reference: Major Trauma is the missing link between basic trauma management and advanced specialist care. Advanced Trauma Life Support courses have revolutionised trauma care in the last 3 decades, but there is little advice for the key decision makers in trauma care once the primary and secondary surveys are complete. This volume is a practical and evidence-based desk reference, giving a comprehensive walk-through from the initial phases of injury, through key decision-making in the resuscitation room, to surgical principles and rehabilitation. Including chapters on damage control, ballistic and blast injuries, and bariatric trauma, this text covers all the main areas of trauma care necessary for the trauma specialist in the 21st Century. The Oxford Desk Reference emphasises practical help but also covers the evidence and science behind trauma management. It includes the most up-to-date guidance from national bodies making recommendations for trauma care, using an international team of contributing authors. This book will become an essential tool for everyday use in the management of trauma.